Where Shrimp Eat Better than People Globalized Fisheries, Nutritional Unequal Exchange and Asian Hunger - Dunaway, Wilma (Brill, 2022)
East, South and Southeast Asia are home to two-thirds of the world's hungry people, but they produce more than three-quarters of the world's fish and nearly half of other foods. Through integration into the world food system, these Asian fisheries export their most nutritious foods and import less healthy substitutes. Worldwide, their exports sell cheap because women, the hungriest Asians, provide unpaid subsidies to production processes. In the 21st century, Asian peasants produce more than 60 percent of the regional food supply, but their survival is threatened by hunger, public depreasantization policies, climate change, land grabbing, urbanization and debt bondage.